2020
DOI: 10.1007/s12026-020-09156-2
|View full text |Cite
|
Sign up to set email alerts
|

Immune characteristics distinguish patients with severe disease associated with SARS-CoV-2

Abstract: This single-center, retrospective study aimed to explore the immune characteristics of COVID-19 and biomarkers to predict the severity of this disease. Patients infected with SARS-CoV-2 (n = 215) treated at the First Affiliated Hospital of Nanchang University from January 24 to March 12, 2020, were included in the study and classified into severe and non-severe groups. Peripheral immunocyte count and cytokine statuses were compared. The correlation between immune status, cytokine levels, and disease severity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Recent SARS-CoV-2 studies have revealed pyroptotic events in infected monocytes using NLRP3 inflammasome activation, contributing to release of pro-inflammatory cytokines through lytic monocyte death (29,80). Significantly elevated levels of monocyte-associated chemokines CCL2 and CCL8 have been observed, as well as CXCL2 and CXCL8, which function as chemotactic factors for neutrophils ( 7), consistent with clinical data showing elevated neutrophil levels in severe SARS-CoV-2 patients (58).…”
Section: Cytokine Stormsupporting
confidence: 62%
“…Recent SARS-CoV-2 studies have revealed pyroptotic events in infected monocytes using NLRP3 inflammasome activation, contributing to release of pro-inflammatory cytokines through lytic monocyte death (29,80). Significantly elevated levels of monocyte-associated chemokines CCL2 and CCL8 have been observed, as well as CXCL2 and CXCL8, which function as chemotactic factors for neutrophils ( 7), consistent with clinical data showing elevated neutrophil levels in severe SARS-CoV-2 patients (58).…”
Section: Cytokine Stormsupporting
confidence: 62%
“…The studies' risk of bias, as measured on the Newcastle-Ottawa Scale, as suggested by Bazerbachi 2018 [10], ranged from 2/5 [19,45] to 5/5 [15,20,23,24,29,37,43,[46][47][48][49], with higher scores indicating lower risk of bias (Table 2). All evaluated studies succeeded in excluding PLOS ONE cases that were not pertinent to the research question.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…The TMPRSS2 facilitates hCoVs, including SARS-CoV-2 infections via two independent mechanisms: (i) proteolytic cleavage of hACE2R which promotes viral uptake, and (ii) CoV Spike proteins cleavage which triggers glycoprotein activation for host cell entry. [72] It has also been suggested that the gut is a potential site of SARS-CoV-2 replication. Besides, TMPRSS2 and TMPRSS4 were seen to facilitate SARS-CoV-2 spike fusogenic activity, thereby promoting virtual entrance into the host.…”
Section: Discussionmentioning
confidence: 99%